A new protocol using a light‐emitting fabric for PDT of AK. (1st April 2019) - Vicentini, C.; Vignion‐Dewalle, A.S.; Thecua, E.; Lecomte, F.; Maire, C.; Deleporte, P.; Béhal, H.; Kerob, D.; Duhamel, A.; Mordon, S.; Mortier, L.
Summary: Actinic keratoses (AKs) are areas of sun‐damaged skin found mainly on sun‐exposed parts of the body, particularly the backs of the hands and forearms, the face and ears, and the scalp in balding men. They are usually harmless although they can be unsightly or inconvenient, and there is a very small risk of some actinic keratoses progressing to a form of skin cancer called squamous cell carcinoma. There are several possible treatments, including photodynamic therapy (PDT), in which a special light activates a cream called a photosensitiser, which has been applied to the affected area of skin. This treatment kills the abnormal cells in the skin. The photosensitisers approved in Europe for PDT of AKs require either activation by red light three hours after application of the photosensitiser (referred to as C‐PDT) or activation by daylight within 30 minutes following application of the photosensitiser (referred to as D‐PDT). The major drawback of C‐PDT is pain during treatment, whereas D‐PDT is nearly pain‐free due to the short time between photosensitiser application and daylight activation. Unfortunately, D‐PDT requires favourable weather conditions. The authors of this study, who belong to the ONCO‐THAI research unit based in France, therefore tested a way to activate the photosensitiser 30 minutes after application, by red light using a flexible, light‐emitting, fabric‐based device (hereinafter referred to as FLEXI‐PDT). This study aimed to assess whether FLEXI‐PDT is at least as effective as C‐PDT in destroying AK. The authors were also interested in whether pain scores differ between FLEXI‐PDT and C‐PDT. For these purposes, 35 patients with AKs on the scalp were treated with FLEXI‐PDT on one side of the scalp and with C‐PDT on the other side. Patients rated their pain during FLEXI‐PDT and during C‐PDT separately. The response of each AK (complete or incomplete disappearance) was assessed by a dermatologist at three months after treatment. From the analyses of the data collected, the authors showed that FLEXI‐PDT, which can be performed in all weather conditions, is at least as effective as and less painful than C‐PDT in destroying AK.